Neurochemistry of Neurochemicals: Messengers of Brain Functions - Uddin, Md. Sahab; Mamun, Abdullah Al; Kabir, Md. Tanvir; Nasrullah, Md.; Wahid, Ferdous; Begum, Mst. Marium; Labu, Zubair Khalid; Rahman, Md. Sohanur; Islam, Md. Tanjir; Amran, Md. Shah; Abdel-Daim, Mohamed M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Neurochemistry refers to the chemical processes that occur in the brain and nervous system. This section of study determines how neurochemicals influence the network of neural operation. The brain transfers numerous chemical information via neurons to communicate. The main role of neurochemistry activities takes place in the brain, which allows it to perform numerous actions. Foundation of brain is a little bit different from man to man and several things can play a role in the levels of various neurotransmitters in the brain. It is supposed that differences in brain chemistry may accountable for a variety of behavioral disorders. A particular cell called neurons is the basis of brain. Neurotransmitters have the capability that it can trigger when ordered to do so, along with receptors for specific neurotransmitters. By sending messages with neurotransmitters to signal various cell activities, brain perform its functions. Neurotransmitter spreads chemical messages from neuron to neuron to broadcast certain work and thus it works. A neuron may accept many chemical messages, both positive and negative from the other neurons contiguous it. They are accountable to get the neuron to reply in different ways, or they may work combine to produce a certain effect. Since all of this occurs just within a split second, the neurotransmitter must be cleared away rapidly so that the same receptors can be activated again and again. Psychoactive drugs work by briefly influencing a man’s neurochemistry, which thusly causes changes in a man’s mind-set, cognition, perception and behavior. Neuropeptides are endogenous protein molecules that are utilized for neuronal signaling. These molecules exert more prolonged and diverse effects on behavior than neurotransmitters. Therefore the objective of this appraisal is to show study of the brain’s chemical makeup especially neurotransmitters, psychopharmaceuticals, neuropeptides and their activities to nervous tissue.